2009
DOI: 10.1038/modpathol.2008.178
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal changes in fibrolamellar hepatocellular carcinoma detected by array comparative genomic hybridization

Abstract: Fibrolamellar hepatocellular carcinoma is a rare subtype of hepatocellular carcinoma with distinct clinical and histological features, and better survival compared with conventional hepatocellular carcinoma in some but not all series. We performed a comparative genomic hybridization analysis on 11 fibrolamellar carcinomas and correlated the findings with clinicopathologic features and survival. Chromosomal imbalances were identified in six cases (55%), whereas the other five (45%) yielded normal results. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Also using conventional CGH arrays, Kakar et al . found chromosomal imbalances in 6 of 11 (55%) FL-HCC tumors [14]. Although genomic alterations were evident in all samples in our series, the results of Kakar are similar to our bimodal distribution of chromosomal abnormalities, with 9 of 17 primary tumors (53%) having more than 1,000 gene amplifications or deletions, and the remainder having fewer than 100.…”
Section: Discussionsupporting
confidence: 86%
“…Also using conventional CGH arrays, Kakar et al . found chromosomal imbalances in 6 of 11 (55%) FL-HCC tumors [14]. Although genomic alterations were evident in all samples in our series, the results of Kakar are similar to our bimodal distribution of chromosomal abnormalities, with 9 of 17 primary tumors (53%) having more than 1,000 gene amplifications or deletions, and the remainder having fewer than 100.…”
Section: Discussionsupporting
confidence: 86%
“…Several novel emerging tumor markers are available in the diagnostics of HCC with varying value and prognostic significance [1,3,[16][17][18]. Previously, we described for the first time that cholangiocellular carcinoma (CCC) is characterized by high expression of tight junction (TJ) protein claudin (CLDN) 4 in contrast to cHCC [19], which was later confirmed by others [20,21].…”
Section: Introductionmentioning
confidence: 93%
“…discovered overexpression of MAPK, PI3K, RAS, and xenobiotic pathways in FL‐HCCs . Kakar and Wilkens compared CGH profiles of FL‐HCCs and other HCCs; they found that none of the pathways that are frequently mutated in typical HCC, such as TP53, Wnt/β‐catenin, or survivin, are mutated in FL‐HCC . Other genes that are overexpressed in FL‐HCC include aromatase, EGFR, anterior gradient 2, and certain neuroendocrine markers such as PCSK1, neurotensin, calcitonin, and DNER .…”
Section: Comparison Between Fl‐hcc and “Classic” Hccmentioning
confidence: 99%